DUKUNGAN SUAMI DENGAN KEJADIAN DEPRESI PASCA MELAHIRKAN - Tolongan, Cindritsya; Korompis, Grace E.C; Hutauruk, Minar (JURNAL KEPERAWATAN, 2019)
Abstrack : Postpartum is a mother after childbirth will experience some psychological, physical or hormonal changes that can cause the mother to experience stress which can continue to depression, so that postpartum depression can have a negative impact on the baby and mother. The purpose of this study was to determine whether there was a relationship between husband’s support and the incidence of postpartum depression at the Tuminting Health Center. This research method uses a cross sectional design. The sampling technique used purposive sampling technique with a total sample of 50 respondents. Methods of data collection using a husband’s support questionnaire and postpartum depression in the immunization room and maternal maternity to find out about husband’s support and depression after giving birth and statistical tests using the chi square test. The results of the study obtained a p-value of 0.004 (â‰¤ Î± = 0.05) which means that there is a significant difference. The conclusion of the results of this study shows that there is a relationship that occurs in mothers after childbirth if there is no good husband support. Keywords: Husband support wit the incidence of postpartum depression Abstrak : Pasca melahirkan merupakan ibu yang setelah melahirkan akan mengalami beberapa perubahan psikologi, fisik ataupun hormonal yang menyebabkan ibu dapat mengalami stres yang dapat berlanjut hingga depresi, sehingga depresi pasca melahirkan dapat berdampak buruk bagi bayi maupun ibu. Tujuan Penelitian ini adalah untuk mengetahui adakah hubungan dukungan suami dengan kejadian depresi pasca melahirkan di Puskesmas Tuminting. Metode penelitian ini menggunakan desain cross sectional. Teknik pengambilan sampel menggunakan teknik purposive sampling dengan jumlah sampel sebanyak 50 responden. metode pengumpulan data menggunakan kuesioner dukungan suami dan depresi pasca melahirkan di ruangan imunisasi dan bersalin ibu untuk mengetahui dukungan suami dan depresi setelah melahirkan dan uji statistic menggunakan uji chi square. Hasil penelitian di dapat nilai p-value sebesar 0,004 (â‰¤ Î± = 0,05) yang berarti ada perbedaan yang signifikan. Kesimpulan hasil penelitian ini menunjukan bahwa ada hubungan yang terjadi pada ibu setelah melahirkan jika tidak ada dukungan suami yang baik. Kata kunci : Dukungan Suami Dengan Kejadian Depresi Pasca Melahirkan